Early and delayed complications of polypectomy in a community setting: The SPoC prospective multicentre trial. Issue 1 (January 2016) - Amato, Arnaldo; Radaelli, Franco; Dinelli, Marco; Crosta, Cristiano; Cengia, Gianpaolo; Beretta, Paolo; Devani, Massimo; Lochis, Davide; Manes, Giampiero; Fini, Lucia; Paggi, Silvia; Passoni, Giovanni Rubis; et al.
Abstract: Background: Colonoscopic polypectomy is effective in reducing the incidence of and mortality from colorectal cancer, but is not complication-free. Aims: To evaluate the incidence of early and delayed polypectomy complications and factors associated with their occurrence in a community setting. Methods: Web-database collection of patients' and polyp's features in consecutive colonic polypectomies during a 3-month period in 18 endoscopy centres. Results: Data on 5178 polypectomies in 2692 patients (54.3% males, mean age 59 years) were collected. The majority of the polyps were <10 mm (83.5%). Antithrombotic agents were taken by 22.7% of patients, 57.3% of which withheld them before the procedure. Overall, 5 patients experienced perforations (0.2%) and 114 had bleeding (4.2%); the overall complication rate was 4.4%. Early complications were observed in 87 (3.2%); delayed complications (all major bleedings) occurred in 32 (1.2%). At multivariate analysis polyp size (size >10 mm: OR 4.35, 95% CI 5.53–7.48) and, inversely, right-sided location (OR 0.58, 95% CI 0.36–0.94) were correlated with bleeding events. The use of antithrombotics was associated with 5-fold increased risk of delayed bleeding. Conclusions: In the community setting, polypectomy was associated with a 1.4% risk of major complications. Polyp size and, inversely, right-sided location were associated with early bleeding; the use of antithrombotics increased the risk of delayed events.